1987
DOI: 10.1248/cpb.35.4846
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the constituents of Pueraria lobata. III. Isoflavonoids and related compounds in the roots and the voluble stems.

Abstract: Two new isoflavone glycosides, the 8-C-apiosyl(1•¨6) glucosides of daidzein and genistein,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
79
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(91 citation statements)
references
References 0 publications
12
79
0
Order By: Relevance
“…This study demonstrates that the referred fraction is composed mainly of three compounds: the major one that represents 90.69% (by high-performance liquid chromatography) of the total mass is the most active one with respect to termination of pregnancy and identified as puerarin, an isoflavone glycoside reported in the literature (Kinjo et al 1987).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This study demonstrates that the referred fraction is composed mainly of three compounds: the major one that represents 90.69% (by high-performance liquid chromatography) of the total mass is the most active one with respect to termination of pregnancy and identified as puerarin, an isoflavone glycoside reported in the literature (Kinjo et al 1987).…”
Section: Discussionmentioning
confidence: 61%
“…1D and 2D NMR and mass spectral studies identified the active compound as puerarin ( Fig. 1), an isoflavone glycoside reported in the literature (Kinjo et al 1987).…”
Section: Purification and Characterisation Of The Test Compoundmentioning
confidence: 76%
See 1 more Smart Citation
“…Convenient Zemplens deacetylation of 2 with sodium methoxide in methanol gave pure coumestrol, m. p. 368°C (LASCHOBER & KAPPE [1990] found 360°C). Both compounds 1 and 2 were fully characterized by 1 H-NMR spectra; chemical shifts and vicinal coupling constants corresponded to the data already published for coumestrol (TAKEYA & ITOKAWA 1982;KINJO et al 1987) or its diacetate 2 (LE- VAN 1984). The carbon signals in 13 C-NMR spectrum of both coumestrol and di-O-acetylcoumestrol were assigned for the first time using two-dimensional HMQC technique (Table 1).…”
Section: Synthesis and Identification Of Coumestrolmentioning
confidence: 59%
“…Only small amount of the subdued peaks were observed, which showed the irregular characteristics of lecithin. This indicated that genistein might be relevant to lecithin and the effect undermined the crystalline characteristics of genistein [11][12][13].…”
Section: Discussionmentioning
confidence: 99%